Analysis of Company Financial Performance with Economic Value Added (EVA) and Market Value Added (MVA) Methods - Julia Ambarwati; Edi Suswardji (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
This study aims to measure and analyze financial performance using the Economic Value Added (EVA) and Market Value Added (MVA) methods at a life insurance company, namely PT AIA Financial. This type of research is descriptive research with a quantitative approach. This study uses secondary data in the form of the financial statements of PT AIA Financial which are published on the official website of PT AIA Financial. The results of the company's research generally show a negative EVA value in the 2016-2019 period, which means that the company's financial performance has not been good. While the MVA value shows positive results, it means that the company shows that management has succeeded in providing added value through the growth of the market capitalization value of the issued shares or the company is able to sell shares in the market at a premium price.